Study of antibacterial activities of the volatile oil of Nigella sativa Linn on animal model - Ara, Nazma; Khaleque, MA; Choudhury, SAR; Amin, Ruhul (Bangladesh Journal of Physiology and Pharmacology, 2009)
In-vivo antibacterial activity of the volatile oil of Nigella sativa linn was carried out in mice. Mice were infected by inoculation of staph. Aureus and result shows successful iradication of bacterial colony. DOI: 10.3329/bjpp.v22i1.3565 Bangladesh J Physiol Pharmacol 2006; 22(1/2) : 22-24